Evaluation of capillary-active mineral insulation systems for interior retrofit solution. (April 2017) - Zhao, Jianhua; Grunewald, John; Ruisinger, Ulrich; Feng, Shuo
Abstract: Installation of thermal insulation is one of the most effective approaches to improve energy efficiency of the building envelope. Interior insulation retrofit of the masonry construction will change its original thermal and moisture balance, thus a careful pre-phase design is needed to avoid the structural and moisture impairments. This study evaluates the performance of four interior insulation systems with application of the capillary-active mineral materials: autoclaved aerated concrete, calcium silicate, mineral foam, and perlite. Hygrothermal properties of these four materials are experimentally measured and analyzed. They present quite different moisture storage and transport characteristics, which influence the hygrothermal behavior of the refurbished construction. A non-capillary-active polyurethane rigid foam insulation system is also presented for comparison. Moreover, the influence of the indoor humidity on the performance of the insulation systems is investigated. Highlights: Hygrothermal properties of four capillary-active mineral insulations are measured. Moisture behaviors of the mineral insulations are analyzed and compared. The performance of the capillary-active interior insulation systems is assessed. A polyurethane rigid foam insulation system is also presented for comparison. The impact of indoor humidity on the performance of the systems is investigated.